THE PRINCIPAL'S STRATEGY IN INCREASING PARENTAL PARTICIPATION AT SIMATANG UTARA ELEMENTARY SCHOOL, TOLITOLI REGENCY - Ofifa Indah Parawansa (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
Students' educational achievement is greatly supported by parental participation. However, there are still a number of barriers that hinder parental participation in school activities, including busy work schedules, poor communication and a lack of awareness regarding the importance of involvement in their children’s education. The purpose of this study was to describe the approaches taken by the principal to increase parental involvement at Simatang Utara Public Elementary School in Tolitoli Regency. This study employed a descriptive design and a qualitative methodology. The principal, instructors, and students' parents made up the research subjects. Observation, interviews and documentation were used to gather data, which were then analysed using methods for data reduction, data presentation, and conclusion drafting. The findings demonstrated that the principal's approach to boosting parental involvement involves working with the school committee, socialising the value of parents' roles in their children's education, increasing effective communication between the school and parents and involving parents in a variety of school activities. This approach is supported by the principal's dedication, teacher support, and parental understanding of the value of education. Parental busyness, time constraints, and some parents' low involvement in school activities are the impeding obstacles. According to the study's findings, the principal's approach was crucial for boosting parental involvement in order to successfully support the accomplishment of educational objectives.